The Strategy of Agriculture Land Management at Gunungsari Area, Kucur Village, Dau, Malang - Yugo Indah Pertiwi; Kliwon Hidayat; Yayuk Yuliati (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2020)
The purpose of this study is to describe the structure of land ownership and agricultural land management strategies in the Gunungsari region and explore the socio-economic and ecological conditions that drive the selection of existing land management strategies. The case study was chosen as a research design with Gunungsari agricultural land area as the case. Data collection was carried out through in-depth interviews with key informants, semi-structured interviews with sample farmers, field observations and documents. Data were analyzed descriptively qualitatively. The results of the study illustrate that dominant individual agricultural land ownership is fragmented into different plot locations with an area of less than 0.5 hectares. Perennial crop monoculture, annual intercropping, perennial crop intercropping, and mixed gardens are available agricultural land management strategies. Perennial crops as the main crops as well as edge crops are still the dominant choice of farm families, according to the internal uniqueness of each family in their interactions with external factors. This choice has consequences for the current land cover of the Gunungsari region. The actor approach that places social practice as a result of dynamic interactions between the actor's internal conditions and the context of his social-ecological environment is seen as relevant.